History repeats itself in Japan: Failure to learn from rubella epidemic leads to failure to provide the HPV vaccine - Yusuke Tanaka; Yutaka Ueda; Kiyoshi Yoshino; Tadashi Kimura (Taylor & Francis Group, 2017)
Eradication of vaccine-preventable diseases is one of the most important goals of public health interventions. Herd immunity can be established by national vaccination programs. However, once the national vaccination program stops for any reason, unprotected group will be generated depending on an unfortunate year of birth. Currently, there are 2 major concerns regarding vaccine cohort gaps in Japan: one is for the rubella vaccine, the other for the human papillomavirus (HPV) vaccine.